Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Karyawan di Furamaxclusive Resort And Villas Ubud - Wati, Ni Wayan Gita Candra; Sujadi, Dewiwati; Widiantara, I Gusti Agung Bagus (Universitas Triatma Mulya, 2023)
The problem raised in this study is whether compensation (X1) and work environment (X2) affect employee performance (Y) at FuramaXclusive Resort and Villas Ubud. The effect of compensation (X1) and work environment (X2) on employee performance (Y) is the dominant variable affecting employee performance at FuramaXclusive Resort and Villas Ubud. Respondents in this study were the number of employees, namely 89 people. Data collection techniques using questionnaires, interviews, and documentation. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and t-test. The results of the analysis show that the regression model is Y = 4.318 + 0.172X1 + 0.278X2. The conclusion obtained is that compensation (X1) has a positive and significant effect on employee performance (Y), and the environment (X2) has a positive and significant effect on employee performance at FuramaXclusive Resort and Villas Ubud. The effect of compensation (X1) and work environment (X2) on employee performance (Y) is 46.0%, while the remaining 54.0 is explained by variables not examined in this study. The work environment variable (X2) has a dominant effect on employee performance (Y) at FuramaXclusive Resort and Villas Ubud.